Lustrous Material Appearances: Internal and External Constraints on Triggering Conditions for Binocular Lustre. (February 2014) - Mausfeld, Rainer; Wendt, Gunnar; Golz, Jürgen
Lustrous surface appearances can be elicited by simple image configurations with no texture or specular highlights, as most prominently illustrated by Helmholtz' demonstration of stereoscopic lustre. Three types of explanatory framework have been proposed for stereoscopic lustre, which attribute the phenomenon to a binocular luminance conflict, an internalised physical regularity (Helmholtz), or to a disentangling of "essential" and "accidental" attributes in surface representations (Hering). In order to investigate these frameworks, we used haploscopically fused half-images of centre-surround configurations in which the luminances of the test patch were dynamically modulated. Experiment 1 shows that stereoscopic lustre is not specifically tied to situations of a luminance conflict between the eyes. Experiment 2 identifies a novel aspect in the binocular temporal dynamics that provides a physical basis for lustrous appearances, namely the occurrence of a temporal luminance counter-modulation between the eyes. This feature sheds some light on the internal principles underlying a disentangling of "accidental" and "essential" surface attributes. Experiment 3 reveals an asymmetry between a light and a dark reference level for the counter-modulations. This finding again suggests an interpretation in terms of an internalised physical regularity with respect to the dynamics of perceiving illuminated surfaces.